Effect of various concentrations of tetracycline hydrochloride demineralization on root dentin surface: A scanning electron microscopic study - Tanuja Penmatsa; Satish Varma; Mythili; Killi Prabhakar Rao; Trinath Kishore; Hima Bindu (Wolters Kluwer Medknow Publications, 2013)
Introduction: Within the last 20 years root demineralization has attracted attention as a periodontal regenerative technique. Topical tetracycline application has been widely reported for use as a conditioner, to decontaminate the root surface and to promote periodontal regeneration. The purpose of this scanning electron microscopic (SEM) study is to evaluate the surface characteristics of demineralized diseased and non-diseased dentine root surfaces using different concentrations of tetracycline hydrochloride (TTC-HCl). Material and Methods: This SEM study was carried out in 20 dentin samples obtained from non-diseased human premolars and 20 dentin samples obtained from diseased human premolars. Pure TTC-HCl was applied to the dentin surface at 50 mg/ml, 100 mg/ml and 150 mg/ml concentrations for 3 min in experimental groups while distilled (0 mg/ml) water was applied to the control groups. Statistical Analysis: Mean and standard deviation were estimated from the sample for each study group. Mean values were compared by either one-way ANOVA with Tukey-Honestly significant difference procedure or Kruskal - Wallis one way ANOVA with Mann-Whitney u-test. Further Student's independent t-test/Mann-Whitney u-test was used appropriately to compare the mean values between two independent groups. Results: In the present study using 100 mg/ml tetracycline seems to be more effective on both diseased and non-diseased dentin surfaces. Conclusions: The results of this study confirm that pure TTC-HCl conditioning produced comparable surface characteristics on dentin of both diseased and non-diseased roots with 100 mg/ml concentration for 3 min.